Pengaruh Gender, Beban Kerja, dan Work-Life Balance Terhadap Stres Kerja (Studi Pada Dosen Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Sonia Amalia Rofi`ah; Khalikussabir Khalikussabir; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2026)
Abstract The increasing demands of the Tri Dharma of Higher Education, combined with rapid technological advancements, have intensified lecturers’ workload and blurred the boundaries between professional and personal life, potentially leading to job stress that affects well-being and productivity. Job stress among lecturers is a complex phenomenon influenced by various factors, yet previous studies on the effects of gender, workload, and work-life balance have produced inconsistent findings. This study aims to examine the influence of gender, workload, and work-life balance on job stress among lecturers at the Faculty of Economics and Business, Universitas Islam Malang. The study employed a quantitative approach, with 54 lecturers selected through proportionate stratified random sampling. Using SPSS 30, data were analysed using multiple linear regression after being collected through a Likert-scale questionnaire. The results indicate that gender, workload, and work-life balance simultaneously have a significant effect on job stress. Partially, workload has a positive and significant effect, while work-life balance has a negative and significant effect. Gender does not have a significant effect. These findings highlight the importance of effective workload management and the promotion of work-life balance to reduce job stress and support lecturers’ well-being. Keywords: Gender, Work load, Work-Life Balance, Work Stress, Lecturers.